TRUS Biopsy Yield in Indian Population: A Retrospective Analysis - Patil, Sunil Raghunath (J Clin Diagn Res, 2017)
INTRODUCTION: The reported cancer detection rate of Trans-Rectal Ultrasonography (TRUS) biopsies (TRUS biopsy yield) has been around 30 percent in western countries. However it is much lower in Asian countries, including India. Hence a larger proportion of patients in India undergo unnecessary biopsies. AIMS: To find out the cancer detection rate of TRUS biopsy (TRUS biopsy yield) in contemporary Indian population. Also, to study the positive predictive values at different serum Prostate-Specific Antigen (PSA)/PSA Density (PSAD) cut off levels and suspicious Digital Rectal Examination (DRE) findings. MATERIALS AND METHODS: This retrospective study was carried out in a tertiary care institute. All symptomatic patients who underwent TRUS guided biopsy for indication of raised serum PSA level (>4 ng/ml) or suspicious DRE findings (nodule, irregularity, hard consistency, immobile rectal mucosa) from January 2012 to December 2014 were included. For serum PSA range (4-10) ng/ml, TRUS guided biopsy was done in patients with percent free/total PSA < 25. Statistical analysis used were Chi-square test, Mann-Whitney U-test, Spearman’s rank correlation analysis and Receiver-Operating Characteristic (ROC) curve. RESULTS: Out of the 235 patients included, 60 patients had malignancy (overall cancer detection rate= 25.53%). The cancer detection rate for PSA ranges of (4-10) and (10-20) ng/ml was as low as 5.95% and 13.16% respectively. Patients with malignant disease had significantly smaller prostate gland size than patients with benign disease (53.89 vs 63.06; p-value <0.05). On the other hand, cancer detection rate was 100% for PSA greater than 50ng/ml. The cancer detection rates were only upto 10% for PSA density ranges upto 0.25 ng/ml/cm(3). The Area Under the Curve (AUC) for PSA and PSAD was 0.876 and 0.884 respectively. Only one patient (0.43%) had post-biopsy complication (acute bacterial prostatitis) requiring hospital admission. CONCLUSION: The current serum PSA and PSAD cut offs of 4 ng/ml and 0.15 ng/ml/cm(3) need to be raised for Indian population to increase its positive predictive value. Prospective study validation of this finding is lacking.